SOSIALISASI PENGEMBANGAN UMKM MELALUI PENINGKATAN KUALITAS PRODUK DI DESA SUKAJAYA MALANGBONG KABUPETEN GARUT - Suharyanto; Herlina, R. Lisye; Widjaja, Warkianto; Juhana, Riyadi; Taufik, M. Irham; Nafia, Isya; Putra, Daniel P (LPPM UKRI, 2026)
The business climate has improved significantly since the COVID-19 pandemic. Community-based businesses, including MSMEs, both in urban and rural areas, have grown significantly. The Indonesian government has also devoted significant attention to MSMEs by establishing a Ministry of MSMEs at the central level and relevant MSME agencies at the provincial and district/city levels. The development of MSMEs in Garut Regency and Malangbong District has been met with great enthusiasm by the community. Traditional Garut MSME products, already in thriving form, are now expanding with improved styles, flavors, and attractive packaging. Furthermore, their quality has also improved. This improvement in quality also opens up opportunities for increased marketing of these products.